Extended immunophenotyping reference values in a healthy pediatric population. Issue 3 (17th October 2018) - Garcia‐Prat, Marina; Álvarez‐Sierra, Daniel; Aguiló‐Cucurull, Aina; Salgado‐Perandrés, Sandra; Briongos‐Sebastian, Sara; Franco‐Jarava, Clara; Martin‐Nalda, Andrea; Colobran, Roger; Montserrat, Isabel; Hernández‐González, Manuel; Pujol‐Borrell, Ricardo; Soler‐Palacin, Pere; et al.
Abstract : Background: For the accurate diagnosis of immunodeficiencies is crucial to compare patients' immunology laboratory values with age‐sex matched controls, yet there is a paucity of normal values for most populations. Objectives: To define appropriate reference values of extended lymphocyte subpopulations and T‐cell receptor excision circle (TRECs) levels in healthy pediatric donors between 1 month and 18 years of age. Methods: Extended immunophenotyping values were obtained by analysis of multiparameter flow cytometry panels for the following subpopulations: CD4+ and CD8+ Naive, Effector, Effector Memory and Central Memory, T helper subpopulations and their degrees of activation, T Regulatory cells, Recent Thymic Emigrants (RTE), B Lymphocyte subpopulations (Transitional, Naive, Preswitch‐Memory, Switch‐Memory, Plasmablasts, CD21low, and Exhausted), and subpopulations for Monocytes, NK cells and Dendritic Cells. Results: Median values and the 10th and 90th percentiles were obtained for 32 lymphocyte and monocyte subpopulations, and for TRECs levels in each age group of children. Naive CD4+ and CD8+ T‐cell populations tended to decrease with age, with significant difference between the groups, in parallel with the reduction in thymic function assessed by TRECs counts and the recent thymic emigrant population. Relative numbers of Th cell populations tended to increase with age. The percentage of class‐switched B cell populations showed a significant increase between the youngest group and the others. Conclusion: This study provides essential data for interpreting extended immunophenotyping profiles in the pediatric and young adult populations, which could be of value for the diagnosis of PIDs and immune‐mediated diseases, particularly those associated with subtle immunological abnormalities. © 2018 International Clinical Cytometry Society